BRD4 inhibition by JQ1 prevents high-fat diet-induced diabetic cardiomyopathy by activating PINK1/Parkin-mediated mitophagy in vivo. (December 2020) - Mu, Jing; Zhang, Donghong; Tian, Yunli; Xie, Zhonglin; Zou, Ming-hui
Abstract: BRD4 is a member of the BET family of epigenetic regulators. Inhibition of BRD4 by the selective bromodomain inhibitor JQ1, alleviates thoracic aortic constriction-induced cardiac hypertrophy and heart failure. However, whether BRD4 inhibition by JQ1 has therapeutic effect on diabetic cardiomyopathy, a major cause of heart failure in patients with Type 2 diabetes, remains unknown. Here, we discover a novel link between BRD4 and PINK1/Parkin-mediated mitophagy during diabetic cardiomyopathy. Upregulation of BRD4 in diabetic mouse hearts inhibits PINK1/Parkin-mediated mitophagy, resulting in accumulation of damaged mitochondria and subsequent impairment of cardiac structure and function. BRD4 inhibition by JQ1 improves mitochondrial function, and repairs the cardiac structure and function of the diabetic heart. These effects depended on rewiring of the BRD4-driven transcription and repression of PINK1. Deletion of Pink1 suppresses mitophagy, exacerbates cardiomyopathy, and abrogates the therapeutic effect of JQ1 on diabetic cardiomyopathy. Our results illustrate a valid therapeutic strategy for treating diabetic cardiomyopathy by inhibition of BRD4. Abstract : Graphic abstract Unlabelled Image Highlights: BRD4 inhibition by JQ1 activates PINK1/Parkin-mediated mitophagy JQ1 exerts therapeutic effect on HFD-induced diabetic cardiomyopathy mouse model Pink1 deletion suppresses mitophagy, exacerbates cardiomyopathy, and abrogates the therapeutic effect of JQ1 on diabetic cardiomyopathy